miR-23c regulates wound healing by targeting stromal cell-derived factor-1α (SDF-1α/CXCL12) among patients with diabetic foot ulcer - Amin, Karan Naresh; Umapathy, Dhamodharan; Anandharaj, Arunkumar; Ravichandran, Jayasuriya; Sasikumar, Changam Sheela; Chandra, Sathish Kumar Rajappan; Kesavan, Rajesh; Kunka Mohanram, Ramkumar (Microvascular research, 2020)
Diabetic Foot Ulcer (DFU) is the most common in patients who have diabetic peripheral neuropathy and angiopathy as well as a foot deformity. The delayed process of wound healing in diabetic condition is mainly due to reduced expression of the growth factors, persistent inflammatory response and endothelial dysfunction. Emerging evidence indicate that miRNAs play a crucial role in regulating angiogenesis, collectively called as “angiomiRs”. The present study aimed to screen the expressions of angiomiRs particularly miR23 family and its association with the various angiogenic factors including SDF-1α in the tissue biopsies isolated from DFU patients. Among the 40 enrolled subjects for this study, 10 were subjected in each group as healthy controls, type 2 diabetic subjects (T2DM), T2DM subjects with uninfected DFU, and T2DM subjects with infected DFU. The expression of both the miR23 family such as hsa-miR-23a, hsa-miR-23b, hsa-miR-23c and angiogenic factors such as SDF-1α, HIF-1α, VEGF, eNOS were investigated in peripheral blood mononuclear cells and tissue biopsy samples using qPCR. We found that the angiogenic factor SDF-1α was significantly decreased in both the circulation and tissue biopsies of patients with T2DM and infected DFU. The SDF-1α at the 3′-untranslated region pairs with target miRNAs namely hsa-miR-23a-3p, hsa-miR-23b-3p and hsa-miR-23c as established using miRNA target prediction algorithm. Further, the tissue-specific expressions of miR-23a and miR-23b were found to be low whereas miR-23c was increased in patients with infected DFU. Moreover, correlation analysis showed that SDF-1α was found to have a significant inverse association with miR-23c. In conclusion, miR-23c may function as a new regulator to inhibit angiogenesis by targeting SDF-1α. [Display omitted] •miRNAs play a crucial role in regulating angiogenesis, collectively called as “angiomiRs”•The angiogenic factor SDF-1α was significantly decreased in patients with T2DM and infected DFU•The tissue-specific expressions of miR-23a and miR-23b were low whereas miR-23c was increased in patients with infected DFU•Correlation analysis showed that SDF-1α was found to have a significant inverse association with miR-23c•miR-23c may function as a new regulator to inhibit angiogenesis by targeting SDF-1α